Teaching Embedded Microprocessor Systems by Enquiry-Based Group Learning - Barnes, M.; Bailey, M.; Green, P. R.; Foster, D. A. (International journal of electrical engineering & education, 2006)
Engineers today are required both to have a mastery of ‘traditional’ technological skills and to be competent with a variety of ‘soft skills’ such as teamworking and the ability to present or sell their ideas. At the same time the technological skill requirements are broader. There is a gradual shift from knowledge of specialist fields, to engineers with a fluency in system integration and embedded system design. This paper describes the development of an undergraduate module in embedded systems design. The learning approach taken is that of a cooperative, enquiry-based project to build a small robot. This allows both technical skills and soft skills to be developed in a supportive environment. The student team is required to plan the design and construction of hardware and software for a unit built around an inexpensive commercial microcontroller. This paper describes the module design rationale, the structure given to the students, their performance and evaluates the educational results of what was a well-received learning activity.